Booster Dose of Bacille Calmette-Guérin Vaccine for Tuberculosis in Low and Middle-Income Countries: A Systematic Review - Oduwole OA; Mwankon JP; Okebe J; Esu EB; Chibuzor M; Sallahdeen A; Arikpo DI; Meremikwu C; Effa EE; Meremikwu MM (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: The Bacille Calmette-Guérin (BCG) vaccine, given as a single dose, offers variable protection against Tuberculosis (TB). It is plausible that repeat doses could improve the effectiveness of the BCG vaccine in settings where the population remain at risk of the disease. Objective: To assess the effectiveness of BCG revaccination as a booster dose in preventing TB in Low- and Middle- Income Countries (LMICs). Methods: We searched the electronic databases without language or publication restrictions and followed the procedures for preparing systematic reviews, including assessing the risk of bias as outlined in the Cochrane handbook. We included randomised controlled trials (RCTs) conducted in LMICs involving children and adults receiving one or more BCG vaccine doses after the primary BCG vaccination. The incidence of severe forms of TB, active TB and adverse events were the primary outcomes. Results: Five RCTs were included in this systematic review. Revaccination with BCG probably makes little or no difference to the risk of active TB measured after five years (Relative risk (RR) 1.16, 95% CI 0.88 to 1.51; 348,083 participants; one study, moderate certainty evidence) or nine years post-revaccination (RR 0.96, 95% CI 0.82 to 1.12; 348,083 participants; one study, moderate certainty evidence). In populations with HIV co-infection, revaccination probably increases the risk of pulmonary tuberculosis compared to placebo (RR 1.74, 95% CI 1.00 to 3.01; 46,764 participants; one study, moderate certainty evidence). Conclusion: The available evidence suggests that BCG revaccination probably makes little or no difference in preventing tuberculosis disease in LMICs.